Using intercultural videos of direct contact to implement vicarious contact: A school-based intervention that improves intergroup attitudes - Vezzali, L; Di Bernardo, GA; Stathi, S; Visintin, EP; Hewstone, M (SAGE Publications, 2018)
We aimed to create an engaging and dynamic intervention for schools that uses videos of direct school peer contact to implement a vicarious contact intervention. Participants were ethnic majority (Italian) and minority (immigrant) high school students (N = 485; age ranging from 14 to 22 years old, Mage = 17.24 years), who were asked to watch and evaluate videos created by peers from their school for a competition for the best video on intercultural friendships. Results revealed that vicarious contact, relative to a control condition where participants were not shown any videos, improved outgroup attitudes, reduced negative outgroup stereotypes, and increased willingness to engage in contact with the outgroup. These effects only emerged when intercultural friendships in the videos were salient. Inclusion of the other in the self, but neither intergroup anxiety nor fear of rejection by the outgroup, significantly mediated the effect of the videos on outcomes. We discuss theoretical and practical implications of the findings.